Izmeneniya paleosredy shel′fov modey Laptevykh i Karskogo v khode poslelednikovoy transgressii - po iskopaemym ostrakodam i foraminiferam (Paleoenvironmental changes of the Laptev and Kara shelves during the postglacial transgression - on the basis of fossil ostracods and foraminifers, in Russian) - Taldenkova, Ekaterina E.; Baukh, Kh. A.; Stepanova, A. Yu.; Pogodina, I. A.; Ovsepyan, Ya. S.; Zimstikh, J. (Izdat. Moskovskogo Universiteta, 2009)
Fossil ostracods and foraminifers were investigated in postglacial sediment sequences from river apeovalleys of the Laptev and Kara Sea shelves. The AMS14C-dated cores recovered from water depths between 60 an 21 meters cover an age range back to 12.2 cal.ka. In the coresfrom the outer-middle shelf, an upcore change of fossil assemblages from brackishwater estuarine to modern marine ones evidences environmental changes related to sea-level rise and shelf flooding. Although the overall succession of fossil assemblages is similar in all studied cores, their timing is different in accordance with spedific water depths of the sites, distance from the coast, river runoff influence and bottom hydrodynamics. Sediment seuquence from the modern inner shelf region was accumulated during the last 6 cal.yrs contains a modern-like inner-shelf assemblage dominated by shallow-water marine and river-proximal species. On the middle-outer shelf, the presence of relatively deep-living benthic species in fossil assemblages of both the early and late stagesof shelf inundatons evicences the influence of bottom reversed currents transferring Atlantic-derived waters onto the shelf. In the late Holocene, a simultaneous increase in relative abundance of both, the deep-living and river-proximal, species recorded in the outer-shelfcores evidencing surface water cooling, increasing ice cover extent and enhanced wind-induced estuarine circulation. In the inner shelf region, periodic strengthening of marine influence in the bottom-water layer is reflected by an increase in the total abundance and diversity of microfossils, as well as proportional representation of relatively deep-living species including planktic foraminifers. Stronger marine influence in the bottom-water layer is often coincident with increasing surface-water freshening. Thus, theses facts also point to an intensification of estuarine circulation on the Laptev and Kara shelves and increasing ice cover extent especially during the time interval 2-4 cal.ka.